Why does idiosyncratic risk increase with market risk? - Söhnke M. Bartram; Gregory W. Brown; René M. Stulz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
From 1963 through 2015, idiosyncratic risk (IR) is high when market risk (MR) is high. We show that the positive relation between IR and MR is highly stable through time and is robust across exchanges, firm size, liquidity, and market-to-book groupings. Though stock liquidity affects the strength of the relation, the relation is strong for the most liquid stocks. The relation has roots in fundamentals as higher market risk predicts greater idiosyncratic earnings volatility and as firm characteristics related to the ability of firms to adjust to higher uncertainty help explain the strength of the relation. Consistent with the view that growth options provide a hedge against macroeconomic uncertainty, we find evidence that the relation is weaker for firms with more growth options.
urn:nbn:de:hebis:30:3-410505
Keywords: G10; G11; G12; 330; uncertainty; idiosyncratic risk; market risk; growth options; liquidity; limits to arbitrage